Why Link Knowledge Management, Organizational Culture and Ethics: Inquiring Results - Costa, Gonçalo Jorge Morais da (2014)
This paper aims to understand how the interaction between knowledge management, organizational culture and ethics occur, focusing on the potential tensions between personal and collective knowledge in learning organizations. These tensions are reflected upon ethical and social dilemmas which are often neglected by managers and produce unexpected impacts into the organizational strategy. Therefore, this contribution is divided into two main sections: knowledge management (levels, dimensions, and ethical issues/social dilemmas); empirical procedures (methodological design, data collection methods, and empirical outcomes). However, in order to promote a reliable argument, this manuscript will shed some light about the underlying topics. Knowledge management (KM) can be characterized as the acquisition and utilization of resources to generate a milieu in which information is available to all, allowing individuals to obtain, share and employ that information to increase their own knowledge and apply their knowledge for organizational benefit. Despite this consideration, KM as a strategy encompasses two antagonistic levels of analysis: personal knowledge management (PKM) and organizational knowledge management (OKM), leading to potential tensions. Moreover, the “knowledge continuum process” is synchronized throughout organizational culture, technology, and ethics. As a result, it is fundamental to approach the ethical issues (free access to organizational knowledge, autonomy, dignity, privacy, intellectual property, fair compensation), and social dilemmas (organizational trust) that literature claims. Moving forward, this research project unites descriptive and explanatory assumptions through an interpretative and critical epistemological study. Additionally, an embedded multiple-case study with grounded theory (multi-method) will be under scrutiny. Nevertheless, the complex and sensitive nature of the research imposes challenges regarding data collection methods (interviews and questionnaires), leading to protocol fine-tune in order to improve the level of confidence. In spite of these constraints, the empirical outcomes clearly demonstrate that a wide range of ethical issues and social dilemmas occur within organizational contexts, which managers do not recognize or neglect.